Releasing the socio‐imagination: children's voices on creativity, capability and mental well‐being. Issue 4 (2nd November 2020) - Stephenson, Lisa; Dobson, Tom
Abstract : With increasing concerns in the UK about the positive mental well‐being and flourishing of children, this research, using drama and creative writing with primary school teachers, children and a theatre company, looks at the links between creative processes and children's well‐being. This pedagogy applies a capability approach and we use this lens to examine children's critical reflections on the project. Interview data highlight the link between agency, social imagination and subjective well‐being. The study offers some concrete examples of the ways in which creative processes can move beyond an outcome‐based understanding of the curriculum by offering a legitimate space for children to explore their values and develop competencies which are crucial for well‐being in the 21st century.